The effectiveness of the integration between the two strategies (the cube and the circular house) on the achievement of fourth grade female students in biology and the development of their supra-cognitive thinking. (Journal of the College of Basic Education, 2022)
The current research aims to know the effectiveness of the integration between the two strategies (the cube and the circular house) on the achievement of fourth-grade female students in biology and the development of their meta-cognitive thinking. Therefore, the researchers used the semi-experimental design of four groups (three experimental groups and the fourth control group). And to achieve the objectives of the research, the researchers formulated the zero opportunities